Student Facilitator Learning Model and Concept Map-Assisted Explanation on Interests and Learning Outcomes of Elementary School Students - Putu Ayu Diah Anggraini; I Made Ardana; I Made Gunamantha (Journal of Psychology and Instruction, 2023)
Teachers have not used innovative learning models and learning is still focused on teachers. The learning provided by the previous teacher was only from parables which made students less understanding of the material given by the teacher. This study aims to analyze the effect of the concept map-assisted SFAE learning model on the interest and learning outcomes of science in grade V students. The total population of this study was 175 students, the sample was 63 students. Learning interest data was collected by questionnaires, while science learning outcomes data were collected by tests. The results of the analysis show: 1) The first hypothesis with Fcount is 173.029 (p < 0.05). 2) The second hypothesis with a Fcalculate of 22.496 (p<0.05). And 3) The third hypothesis with a Fcalculate of 90.955(p<0.05). Based on these results, it can be concluded that there are significant differences in interest and science learning outcomes between groups of students who are taught with the Student Facilitator And Explaining learning model assisted by concept maps and groups of students who are not taught with the Student Facilitator And Explaining learning model assisted by concept maps in grade V elementary school students.